2017
DOI: 10.1007/s11192-017-2333-y
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling in scientific fields

Abstract: Allometric scaling can reflect underlying mechanisms, dynamics and structures in complex systems; examples include typical scaling laws in biology, ecology and urban development. In this work, we study allometric scaling in scientific fields. By performing an analysis of the outputs/inputs of various scientific fields, including the numbers of publications, citations, and references, with respect to the number of authors, we find that in all fields that we have studied thus far, including physics, mathematics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…number of new patents [17] and inventions [18]) tends to be superlinear compared to city size, with an allometric growth exponent greater than 1. Furthermore, Rocha et al found that the number of social interactions in animal groups, including humans and other mammals, also exhibit a superlinear allometric growth relationship with group size [19].…”
Section: J Stat Mech (2023) 083404mentioning
confidence: 99%
“…number of new patents [17] and inventions [18]) tends to be superlinear compared to city size, with an allometric growth exponent greater than 1. Furthermore, Rocha et al found that the number of social interactions in animal groups, including humans and other mammals, also exhibit a superlinear allometric growth relationship with group size [19].…”
Section: J Stat Mech (2023) 083404mentioning
confidence: 99%
“…Shen et al (2016) apply a citation input-output analysis to study the influence of physics subfields. Dong et al (2017) include other factors, including number of co-authors per article and number of publications in subfields of mathematics, physics, and economics. Other factors might include grant funding and faculty surveys.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Several studies have investigated the emergence and evolution of scientific fields, from the discovery of new concepts to their adaptation and modification by the scientific community [ 1 – 6 ], to the slow-down in their growth due to the ever rising number of publications [ 7 ]. In particular, methods ranging from bibliometric studies [ 8 , 9 ] to network analyses [ 6 , 10 , 11 ] and natural language processing [ 12 14 ] have been implemented on large publication corpora to monitor the propagation of concepts across articles [ 15 17 ] and the social interactions between researchers that are producing them [ 11 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%